Prinsip Pembuktian Perkara Tindak Pidana Pencucian Yang Berdiri Sendiri (Stand Alone Money Laundering) - Defid Tri Rizky; Mochamad Kevin Romadhona (Universitas Airlangga, 2022)
AbstractThis research will explain about the nature of the stand alone money laundering’s case handling and the substantiation’s formulation on the stand alone money laundering’s case handling in the future. The urgency of this research is the implementation of principle of proof on the crime of an independent money laundering. The arrangement of this research uses judicial normative method by analizing both the regulations on criminal law in Indonesia and the international provisions regulating the criminal act of money laundering. This research results that in the stand alone money laundering’s case handling can be executed independently without prior process of the prosecution and verdict on its predicate crimes, but in the substantiation’s process remain to need the availability of proof or evidences which can explain the relation between the property assets and the crime resulting those property assets, based on proofing’s principles provided in Article 183 Code of Criminal Procedure (KUHAP) and carried out using indirect evidential (circumstantial evidence). Thus, the provisions on the norms regulating the concept of stand-alone money laundering in the Law Number 8 Year 2010 concerning Prevention and Eradication of Criminal Act of Money Laundering needs to be reformulated. Keywords: Criminal Act; Money Laundering; Princple KUHAP 183; Stand Alone. AbstrakPenelitian ini akan membahas tentang hakikat penanganan perkara stand alone money laundering dan formulasi pembuktian terhadap penanganan perkara stand alone money laundering dalam penanganan perkara di masa yang akan datang. Urgensi penelitian ini adalah implementasi prinsip pembuktian atas tindak pidana pencucian uang yang yang berdiri sendiri. Penyusunan penelitian ini menggunakan metode penelitian yuridis normatif dengan menganalisis peraturan-peraturan pidana di Indonesia maupun ketentuan-ketentuan internasional yang mengatur tentang tindak pidana pencucian uang. Hasil penelitian ini menunjukkan bahwa, penanganan perkara stand-alone money laundering merupakan penanganan perkara pencucian uang secara independen tanpa adanya penuntutan ataupun putusan atas tindak pidana asalnya terlebih dahulu, namun dalam pembuktiannya tetap dibutuhkan adanya bukti yang dapat menjelaskan adanya keterkaitan antara harta kekayaan dengan tidak pidana yang menghasilkan harta tersebut, berdasarkan prinsip pembuktian 183 KUHAP serta melalui bukti tidak langsung (circumstantial evidence). Konsep stand-alone money laundering dalam Pasal 69 Undang-Undang Nomor 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang perlu di reformulasi rumusannya. Kata Kunci: Tindakan Kriminal; Pencucian Uang; Prinsip KUHAP 183; Berdiri Sendiri.